Müller glial microRNAs are required for the maintenance of glial homeostasis and retinal architecture. Issue 1 (December 2017) - Wohl, Stefanie; Jorstad, Nikolas; Levine, Edward; Reh, Thomas
Abstract To better understand the roles of microRNAs in glial function, we used a conditional deletion of Dicer1 (Dicer-CKOMG ) in retinal Müller glia (MG). Dicer1 deletion from the MG leads to an abnormal migration of the cells as early as 1 month after the deletion. By 6 months after Dicer1 deletion, the MG form large aggregations and severely disrupt normal retinal architecture and function. The most highly upregulated gene in the Dicer-CKOMG MG is the proteoglycan Brevican (Bcan ) and overexpression ofBcan results in similar aggregations of the MG in wild-type retina. One potential microRNA that regulatesBcan is miR-9, and overexpression of miR-9 can partly rescue the effects of Dicer1 deletion on the MG phenotype. We also find that MG from retinitis pigmentosa patients display an increase in Brevican immunoreactivity at sites of MG aggregation, linking the retinal remodeling that occurs in chronic disease with microRNAs. Müller glia are a type of retinal glial cell important for maintaining retinal structure and implicated in response to retinal damage. Here the authors identify Brevican, a chondroitin sulfate proteoglycan, as a microRNA-modulated regulator of Müller glia function.